Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Okay, here we have this:
[tex]\begin{gathered} 1/4\mleft(x+2\mright)-1/3\mleft(x-1\mright)=1/2\mleft(x+1\mright) \\ \frac{x+2}{4}-\frac{x-1}{3}=\frac{1}{2}x+\frac{1}{2} \\ \frac{\left(x+2\right)\cdot\:3}{12}-\frac{\left(x-1\right)\cdot\:4}{12}=\frac{1}{2}x+\frac{1}{2} \\ \frac{\left(x+2\right)\cdot\:3-\left(x-1\right)\cdot\:4}{12}=\frac{1}{2}x+\frac{1}{2} \\ \frac{-x+10}{12}=\frac{1}{2}x+\frac{1}{2} \\ -\frac{x}{12}+\frac{10}{12}=\frac{1}{2}x+\frac{1}{2} \\ -\frac{x}{12}+\frac{5}{6}=\frac{1}{2}x+\frac{1}{2} \\ -\frac{x}{12}=-\frac{1}{3}+\frac{1}{2}x \\ -\frac{7x}{12}=-\frac{1}{3} \\ -7x=-4 \\ x=\frac{4}{7} \end{gathered}[/tex]Now, let's check the solution:
[tex]\begin{gathered} 1/4\mleft(x+2\mright)-1/3\mleft(x-1\mright)=1/2\mleft(x+1\mright) \\ 1/4\mleft(\frac{4}{7}+2\mright)-1/3\mleft(\frac{4}{7}-1\mright)=1/2\mleft(\frac{4}{7}+1\mright) \\ \frac{1}{4}(\frac{18}{7})-\frac{1}{3}(-\frac{3}{7})=\frac{1}{2}(\frac{11}{7}) \\ \frac{9}{14}+\frac{1}{7}=\frac{11}{14} \\ \frac{11}{14}=\frac{11}{14} \end{gathered}[/tex]Since the sides are equal, the result (x=4/7) is true.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.